Lectura sociocognitiva de textos en inglés en cursos básicos de la Universidad de Oriente, Venezuela - MSc. Ana R. Coraspe-González (Santiago, 2015)
This paper offers a sociocognitive orientation towards reading of English writings in basic training courses in Universidad de Oriente. The important theoretical components for the development of this research were psychological constructivism and social constructivism. Those came from two main categories: reading as a cognitive activity and reading as a social activity, which supply analysis of professors’ speech. The used methodology was interpretative. Those interpretations from professors’ speech go through reflecting that reading should not be exclusively seen from a cognitive aspect, but it should be related a social view in order to have integrated point of view of what reading written texts means. Inside these reflections, some sociocognitive strategies are suggested to be developed during reading comprehension process of written texts in English. Keywords: sociocognitive strategies, social constructivism, psy-chological constructivism, reading comprehension, English written texts.